KONSTRUKSI BERITA OLAHRAGA PADA MEDIA MASSA INTERNET (ANALISIS FRAMING BERITA KONFLIK MARQUEZ DAN ROSSI PADA SINDONEWS.COM - Armaiga Chandra; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The Internet as a mass media managed to change the human form, from local to global, open to the development of information, to influence their civilization and dubbed the big village, which is a big village. They can get to know each other and greet each other. In this study, SINDOnews.com is an internet mass media site that has a tagline,